Case Report: a giant liposarcoma of the spermatic cord - Wang, Mingshan; Fu, Yong; Liu, Xiaowen; Liu, Zheng (Frontiers in Oncology, 2025)
BackgroundLiposarcoma of the spermatic cord is an extremely rare urological malignancy, with fewer than 300 cases reported in the literature worldwide, and it is often difficult to distinguish from inguinal hernias and epididymal cysts. Typically, it presents as an asymptomatic, slow-growing paratesticular mass.Case presentationThe case described herein involves a 59-year-old man who presented to our hospital with a painless mass in the left scrotum. Physical examination revealed a fixed, firm mass in the left scrotum. Ultrasonography of the scrotum demonstrated an inhomogeneous echogenic mass measuring approximately 113 x 83 x 62 mm on the left side. Testicular MRI showed a mass in the left scrotum measuring approximately 67 x 56 x 98 mm, exhibiting isointence T1 mixed with high T2 signals. The patient then underwent surgery and pathology confirmed a liposarcoma of the spermatic cord. Currently no signs of tumor recurrence on follow-up.ConclusionsLiposarcoma of the spermatic cord is an exceedingly rare condition, for which surgical intervention is the preferred treatment option. While there is no definitive evidence supporting the use of adjuvant radiotherapy following surgery, it remains necessary in cases where surgical margins are uncertain.